THE USAGE OF MULTIMEDIA IMPROVE PHYSICS LEARNING ACHIEVEMENT - ., Esti Wahyuni (Universitas Tanjungpura, 2017)
This study was to show the understanding level of physics lesson by the setudents of SMK SMTI Pontianak wich was still low. The learning of Physics had not been applied through the concept of contextual learning. It was purposeful that the usage of multimedia strengthened the students in learning Physics and made them be more active, innovative, creative, effective and fun. The Usage of multimedia in this classroom action research was able to improve the students’ learning achievement conducted in SMK SMTI Pontianak, Sulawesi Dalam Street Number 31 Pontianak, in the second semester on academic year 2016/2017. A total of 26 students of X-F grade of Industrial Chemistry (IC) played an active role in three cycles of this study. There wass an increase in learning achievement.